An Examination of the Observed Placebo Effect Associated with the Treatment of Low Back Pain – A Systematic Review - Aaron A Puhl; Christine J Reinhart; Elisabeth R Rok; H Stephen Injeyan (Pain Research and Management)
OBJECTIVE: To determine whether the nonspecific effects that occur following the use of sham interventions to treat nonspecific low back pain (LBP) are large enough to be considered clinically meaningful.